The effect of diphenylethane side-chain substituents on dibenzocyclohexadiene formation and their inhibition of α-synuclein aggregation in vitro. (15th January 2023) - Bernardes, Gabriel; Munir, Omer; Krol, Ed S.
Graphical abstract: Abstract: The naturally-occurring di-catechol lignan nordihydroguaiaretic acid (NDGA) and an analog without methyl groups on the butyl linker both undergo intramolecular cyclization at pH 7.4 to form dibenzocyclooctadienes. Both NDGA and these dibenzocyclooctadienes have been shown to prevent in vitro aggregation of α-synuclein, an intrinsically disordered protein associated with Parkinson's disease. NDGA possesses two vicinal methyl groups on the butyl linker and the presence of these methyl groups attenuates the rate of intramolecular cyclization versus the unsubstituted analog, in opposition to the anticipated Thorpe-Ingold effect, likely due to steric repulsions during cyclization. Numerous 1, 2-bis-ethane di-catechols are known to inhibit α-synuclein aggregation in vitro and we hypothesize that these compounds undergo a similar intramolecular cyclization and the cyclized products may be responsible for the activity. To test this hypothesis we prepared a series of 1, 2-bis-ethane di-catechols with 0, 2 and 4 methyl substituents on the linker. We have confirmed that these compounds undergo intramolecular cyclization to form dibenzocyclohexadienes and that steric interactions between the methyl substituents leads to an increase in the rate of intramolecular cyclization, which is in contrast to what was observed for lignan di-catechols. The rate of cyclization to form six-membered rings is 10–30 times more rapid than formation of eight membered rings and the dibenzocyclohexadienes also prevent in vitro aggregation of α-synuclein.